Simultaneously solving process selection, machining parameter optimization and tolerance design problems: A bi-criterion approach - Wang, Pei (University of Ottawa (Canada), 2003)
The selection of right process, use of optimal machining parameters and specification of best tolerance parameters have been recognized by industry as key issues to ensure product quality and reduce production cost. The three issues have thus attracted a great deal of attention over last several decades. However, they are often addressed separately in existing publications. In reality, the three issues are closely interrelated. Analyzing the three issues in isolation will inevitably lead to inconsistent, infeasible, or conflicting decisions. To avoid the drawbacks, an integrated approach is proposed to jointly solve process selection, machining parameter optimization, and tolerance design problems. The integrated problem is formulated as a bi-criterion model to handle both tangible and intangible costs. The model is solved using a modified Chebyshev goal programming method to achieve a preferred compromise between the two conflicting criteria. The application of the proposed bi-criterion approach has been demonstrated by first using the single component single part feature case. The integrated approach is then extended to the multiple components multiple part features case (the assembly case). Examples are provided to illustrate the application of the two models and the solution procedure. The results have shown that the decisions on process selection, machining parameter selection and tolerance design can be made simultaneously using the models.
Keywords: Engineering, Industrial.; Engineering, Mechanical.